An event-driven approach for resources planning in distributed power generation systems. (May 2022) - Maschio, Dierli M.R.; Duarte, Bruno; Lazzaretti, André E.; Lafay, Jean-Marc S.; Adzkiya, Dieky; da Costa, Jean Patric; Teixeira, Marcelo
Abstract: Renewable Energy Sources ( RESs ) stand as a straightforward alternative to complement the energy grid and have been recurrently integrated into the generation and distribution matrices. Physically, generation components have distributed nature and they are expected to work coordinately, complementing each other to supply centralised microgrids, which interface them with the main power grid and consumers. As RESs have intermittent nature, engineers are limited to plan resources consumption, fulfil unit commitments, stratify time, cost, environmental impact, and quality of energy. This paper exploits the event-driven behaviour of microgrids to provide ways for them to recognise their context and cooperate towards common goals. Our main result is a Petri net simulation model that estimates customisation policies to be applied back over the microgridvia event-based control. Results show that in some cases it is possible to save effort (and resources) of power generation by replacing reactiveness for a more balanced, context-aware, energy chain. A real photovoltaic plant is modelled by our approach with 86% accuracy. Highlights: A formal method is developed to control the event-driven behaviour of distributed power system components. A simulation model is proposed to anticipate cooperation policies for generation plants. A case study applies the models for resources planning in a real photovoltaic plant. A literature review is discussed and comparisons are provided wherever possible along the paper.